Desenvolvimento de uma ferramenta numérico computacional para avaliação da propagação sonora em ambientes fechados - Nishida, Pedro Pio Rosa (2022)
It was proposed in this work the development of a computational tool capable of carrying out simulations of sound propagation in closed rooms with results equivalent to those observed in reality and with a lower computational cost. In addition, the possibility of predicting acoustic quality parameters of the rooms was desired. For this, a literature review was carried out with the different methods for acoustic simulation, and evaluated the most suitable for the referred application. Based on this review, the method chosen was the Digital Waveguide Meshes. The formulation of this method was presented, in addition to implementations of new techniques such as mesh interpolation and new formulations for the contours or surfaces of obstacles. The results were, initially, validated with those obtained through the Finite Element Method. A method for measuring the in situ sound absorption coefficient was also studied for use in the acoustic modeling of the different surfaces present in the rooms to be simulated. Finally, simulations and experiments were developed using a room in different configurations for the experimental validation of the results provided by the developed tool. After implementing the code with the solutions to reduce the computational cost and more accurate acoustic modeling, the results were considered experimentally validated, which allows characterizing the tool as accurate, in addition to presenting shorter calculation times and not requiring the allocation of larger amounts of memory for storing the matrices.